The effects of needleless connectors on catheter-related bloodstream infections - Btaiche, Imad F. (2011)
Needleless connectors, including the standard split septum and the luer-activated mechanical valve connectors, have been introduced into clinical practice to eliminate the risk of needlestick injuries by avoiding the use of needles when accessing the intravascular catheters. Negative and positive displacement mechanical valves have been associated with increased rates of catheter-related bloodstream infections as compared with split septum connectors. Based on available data, split septum connectors should be preferentially used instead of mechanical valves. Adequate disinfection by scrubbing the access port preferably with chlorhexidine is recommended to minimize the risk of catheter microbial contamination along with proper infection control practices. Large prospective randomized clinical trials are needed to evaluate further the possible causes and effects of different types of mechanical valve needleless connectors on bloodstream infections.